ВПЛИВ АГРОТЕХНІЧНИХ ЗАХОДІВ НА ЧИСЕЛЬНІСТЬ ТА ФІЗІОЛОГО-БІОХІМІЧНУ АКТИВНІСТЬ МІКРООРГАНІЗМІВ СІРОГО ЛІСОВОГО ҐРУНТУ - Малиновська, І. М. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2018)
The influence of agrotechnical measures: mineral fertilization, liming, dipping of biomass ofgreen manure culture and by-products of the precursor in crop rotation on the number andphysiological-biochemical activity of microorganisms of the root zone of spring wheat was studied.It has been established that the introduction of mineral fertilizers and liming increases the numberof microorganisms of the main ecological and trophic, functional and systematic groups andimproves physiological-biochemical activity of representatives of certain groups ofmicroorganisms. The introduction of exogenous organic matter (green manure + by-products of theprecursor) allows to reduce the number of melanin-synthesizing micromycetes in gray forest soil by7.65 %, their specific content in the total number of micromycetes by 47.4 %, reduce the level ofphytotoxicity of the soil by 43.4 %. Taking into account long-term data on increasing the numberand specific content of melanin-synthesizing micromycetes in soils of contaminated ecotops, thisgroup of microorganisms can be considered as diagnostic in assessing the general level ofanthropogenic pollution of agrophytocenoses.